Review of porosity uncertainty estimation methods in computed tomography dataset - Jaques, Victory; Du Plessis, Anton; Zemek, Marek; Šalplachta, Jakub; Stravová, Zuzana; Zikmund, Tomáš; Kaiser, Jozef (IOP Publishing, 2021)
X-ray computed tomography is widely used for non-destructive testing and analysis in a broad variety of fields. Its main usage is for 3D porosity identification and quantification. This can be achieved through the image segmentation of the reconstructed dataset which can have a huge impact on the porosity value. The most widely used segmentation algorithms are based on global thresholding, which takes the whole volume into account. To ensure a certain level of confidence and reproducibility of the porosity value, a thorough description of the workflow should be available with uncertainty estimation. This workflow description is often insufficient and the uncertainty missing according to a review of the literature. This work provides recommendations on how to report the processing steps for the porosity evaluation based on computed tomography data and reviews methods for the estimation of the porosity measurement uncertainty from the literature.

X-ray computed tomography is widely used for non-destructive testing and analysis in a broad variety of fields. Its main usage is for 3D porosity identification and quantification. This can be achieved through the image segmentation of the reconstructed dataset which can have a huge impact on the porosity value. The most widely used segmentation algorithms are based on global thresholding, which takes the whole volume into account. To ensure a certain level of confidence and reproducibility of the porosity value, a thorough description of the workflow should be available with uncertainty estimation. This workflow description is often insufficient and the uncertainty missing according to a review of the literature. This work provides recommendations on how to report the processing steps for the porosity evaluation based on computed tomography data and reviews methods for the estimation of the porosity measurement uncertainty from the literature.
Review of porosity uncertainty estimation methods in computed tomography dataset
Keywords: Global thresholding; Computed tomography; Uncertainty estimation; Results comparison; Porosity evaluation; Segmentation; Global thresholding; Computed tomography; Uncertainty estimation; Results comparison; Porosity evaluation; Segmentation